Crecimiento y maduración sexual de Astyanax fasciatus (Pisces: Characidae) en el embalse Arenal, Guanacaste, Costa Rica - Mora Jamett, Margarita; Cabrera Peña, Jorge; Alvarado Bogantes, William (Revista de Biología Tropical, 1997)
Growth and sexual maturation of Astyanax fasciatus were studied in shallow areas of the Arenal reservoir in Costa Rica. Von Bertalanffy's equation was 11 = 167.3 (l - e(-0.093 ,- 0.132). The mean growth for the first six months was 11.7 nunlmonth, 6.9 for the six following months, and diminishing to 4.0 mm/month in the followin! months. The relationship between total length and weight was: W = 8.6 x 10- 113.081 for males and W = 1.8 x 10 TI3.434 for females. Males and females attaln sexual maturity al TI between 70 - 80 mm, approximately when they are six months old. The species reproduces a11 year with peak activity between July and September